Coffee Supply Chain Performance Measurement In Ulu Belu District, Tanggamus Regency, Lampung Province - Sylvia, Teny; Wiyono, Teguh; Putra, Endo Pebri Dani; Asrol, Muhammad; Sembiring, Noveliska Br; Yunira, Eka Nur'azmi; Subara, Deni; Devita, Wilda Harlia (Department of Agroindustrial Technology, Faculty of Agricultural Technology UGM, 2025)
Ulu Belu District, as the largest producer of robusta coffee in Lampung Province, faces challenges throughout its coffee supply chain, from cultivation to marketing. This study aims to examine the structure of the coffee supply chain, evaluate its performance using the Supply Chain Operations Reference (SCOR) model combined with the Analytic Network Process (ANP), and recommend strategies for improvement. The identification results reveal that the coffee supply chain in Ulu Belu District involves several key actors, including farmers, commodity aggregators, collectors, business partners, ground coffee processors, domestic roasters, retailers, exporters, and consumers. This supply chain operates through the flow of products, information, and financial resources among these actors. The coffee supply chain performance measurement results in Ulu Belu District indicate a very poor overall performance score of 58.855. Performance at the three supply chain tiers also reflects concerning conditions: farmers scored 59.721, indicating a very poor performance; collectors scored 62.888, reflecting a poor condition; and business partnerships scored the lowest at 53.957, also categorized as very poor. The strategies for improving supply chain performance include providing training and outreach on Good Agricultural Practices (GAP), implementation of GAP and Good Handling Practices (GHP), implementation of the Common Code for the Coffee Community (4C) certification, increasing storage warehouse capacity, implementing Collaborative Planning, Forecasting, and Replenishment (CPFR) in supply chain management in Ulu Belu, determining safety stock, and planning delivery schedules.